Exploring opportunities for holistic family care of parental caregivers of children with life-threatening or life-limiting illnesses. (September 2021) - Bally, Jill MG; Burles, Meridith; Smith, Nicole R; Holtslander, Lorraine; Mpofu, Chris; Hodgson-Viden, Heather; Zimmer, Marcelline
Life-threatening and life-limiting illnesses in children have profound implications for all family members, many of whom experience unmet health and support needs. Guided by literature on family-centered care and an Interpretive Description methodology, qualitative focus group interviews were conducted with 18 parental caregivers and health care and support providers to explore family experiences and identify care and support needs across the illness trajectory. Data analysis resulted in three themes related to parental participation in children's medical care, parental and familial psychological well-being, and social support needs. These inter-related themes reflect the complex nature of family life with childhood illness, highlighting families' holistic needs and how children's physical and psychological care is intertwined with the psychological and social well-being of the family system. Additionally, the findings revealed the significance of communication to parental caregivers' hope, coping, and well-being. The findings add depth to existing literature, and identify opportunities for addressing families' unmet needs, with specific attention to the role that social workers can play in facilitating family-centred care to promote effective support of parental caregivers. As such, the findings emphasize the important contributions that social workers can make within health care teams and in educational settings to optimize parents' ability to care for ill children while maintaining family functioning and well-being, and as advocates for social and policy change.